Lectotypification of Thalictrum cultratum(Ranunculaceae) - Singh, Harsh; Srivastava, Alka; Husain, Tariq (Phytotaxa, 2016)
The genus Thalictrum Linneaus (1753: 545) (Ranunculaceae), commonly known as ‘meadow-rue’, comprises 150 to 200 species distributed in temperate regions (Tamura 1995, Fu and Zhu 2001). It is represented by 25 taxa in India (Rau 1993, Santapau and Henry 1973) mostly confined to the Himalayan region. For one of these species, Thalictrum cultratum Wallich (1831:26), the protologue includes two localities (Gossain Than and Kumaon), but no reference to a type specimen. Riedl and Nasir (1991) cited Wall. Cat. 3715 as type without further specifications.